2021
DOI: 10.3389/fpsyt.2021.635214
|View full text |Cite
|
Sign up to set email alerts
|

Personality Inventory for DSM-5 in China: Evaluation of DSM-5 and ICD-11 Trait Structure and Continuity With Personality Disorder Types

Abstract: The Personality Inventory for the DSM-5 (PID-5) is an established tool for assessing personality disorder (PD) traits that was developed based on section III of the DSM-5. It is composed of 220 items, organized into 25 facets, which are distributed among five domains. The psychometric properties of the Chinese version of the PID-5 remain to be demonstrated. Two samples were embodied in this study that included 3,550 undergraduates and 406 clinical patients. To probe the structure of the PID-5, parallel analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Bach et al (2017) created and investigated an algorithm for the PID-5, which allowed the user to compute a separate ICD-11 trait domain of anankastia by averaging the facet scores for "rigid perfectionism" and "perseveration." This operationalization has been empirically supported and further refined in later studies (Bach et al, 2018;Fang et al, 2021;Hemmati et al, 2021;Lotfi et al, 2018;Lugo et al, 2019;Sellbom et al, 2020). Additionally, other wellestablished instruments such as Minnesota Multiphasic Personality Inventory and computerized adaptive test of personality disorders may also be used to delineate aspects of ICD-11 trait domains (Anderson & Sellbom, 2021;Tarescavage & Menton, 2020).…”
Section: Measuring the Ampd And Icd-11 Trait Modelsmentioning
confidence: 93%
“…Bach et al (2017) created and investigated an algorithm for the PID-5, which allowed the user to compute a separate ICD-11 trait domain of anankastia by averaging the facet scores for "rigid perfectionism" and "perseveration." This operationalization has been empirically supported and further refined in later studies (Bach et al, 2018;Fang et al, 2021;Hemmati et al, 2021;Lotfi et al, 2018;Lugo et al, 2019;Sellbom et al, 2020). Additionally, other wellestablished instruments such as Minnesota Multiphasic Personality Inventory and computerized adaptive test of personality disorders may also be used to delineate aspects of ICD-11 trait domains (Anderson & Sellbom, 2021;Tarescavage & Menton, 2020).…”
Section: Measuring the Ampd And Icd-11 Trait Modelsmentioning
confidence: 93%
“…As Somma et al (2019) demonstrated that the traditional five-factor structure of the PID-5 was replicable across Western country samples, we hypothesized that this structure would be replicable and congruent with the factor structure extracted in the U.S. community sample. As the five-factor structure has been found to produce an adequate fit using CFA across Chinese samples that have used the 220-item PID-5 in adult samples (Fang et al, 2021), we hypothesized that a five-factor solution would be an acceptable fit to the Chinese community sample. Finally, as cultural and sociocontextual differences produce variations in personality across cultural groups, we hypothesized that the five-factor structure in the United States and Chinese samples would be noninvariant.…”
Section: The Present Studymentioning
confidence: 99%
“…We agree and believe that for the AMPD to achieve world-wide universal status it must demonstrate broad-based cultural equivalency across both Western and non-Western countries, cultures, and languages. Although there have been a few studies examining the AMPD model with PID-5 or its brief form in Chinese-speaking samples (see Fang et al, 2021;W. Zhang et al, 2022), the results from these studies are less than consistent and none have directly examined the congruence to the PID-5 factor structure across Chinese and U.S. samples.…”
Section: Antagonism (Ant) Disinhibition (Dis) and Psychoticism (Psy)mentioning
confidence: 99%
See 1 more Smart Citation
“…We used PubMed, PsycINFO, Web of Science, and a broad snowballing method to identify a total of nine relevant studies investigating associations between traditional PD types and ICD-11 trait domain scores (14,17,(24)(25)(26)(27)(28)(29)(30). We chose to include exclusively articles published after 2017, with the rationale being that ICD-11 has gone through a number of iterations, in which diagnostic definitions have undergone significant changes (5,(31)(32)(33)(34).…”
Section: The Current Reviewmentioning
confidence: 99%